2017
DOI: 10.1055/s-0043-109100
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Pharmacology of Ferula hermonis Boiss. – A Review

Abstract: Ferula hermonis, a well-known species of the genus Ferula found in Lebanon and Syria, has a brilliant history in traditional medicine as it has been used for the treatment of erectile dysfunction in men and menopausal disturbances in women. Thanks to modern pharmacological and clinical investigations, is a valuable medicinal and condimental plant that may be used for the treatment of impotence and diabetes, the prevention of osteoporosis, and possesses anti-microbial and anti-inflammatory properties. Phytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Ferula species from the family Apiaceae are rich sources of biologically active natural products including sesquiterpene coumarins (SCs) and sesquiterpenes [48]. Some studies have shown that SCs are able to enhance the cytotoxicity of anticancer compounds [49].…”
Section: Discussionmentioning
confidence: 99%
“…Ferula species from the family Apiaceae are rich sources of biologically active natural products including sesquiterpene coumarins (SCs) and sesquiterpenes [48]. Some studies have shown that SCs are able to enhance the cytotoxicity of anticancer compounds [49].…”
Section: Discussionmentioning
confidence: 99%
“…There is a large number of medicinal species in Iran, and some of the most important ones belong to the genus Ferula (Apiaceae), which includes about 213 species based on The Plant List (2013). In Iran, Ferula is represented by 30 species, of which 15 are endemic (Sattar and Iranshahi, 2017), and almost all of them are perennials. Ferula ovina is an Iranian Ferula , and is spread across vast areas in the eastern and central parts of the country at altitudes of 2000‒4000 m with an average annual precipitation of 350‒700 mm (Safaian and Shokri, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Overall, it was suggested that UMB may contribute to the antioxidant and anti-inflammatory properties of F. persica Willd. [22] Anti-inflammatory effects of UMB in animal models resemble those of non-steroidal anti-inflammatory drugs (NSAIDs), which render UMB an attractive alternative for evaluation in all pain models including neuropathic pain. [16] Chemotherapy-induced neuropathic pain still remains a clinical issue requiring effective treatment, despite the considerable research and efforts directed to this end.…”
Section: Introductionmentioning
confidence: 99%
“…persica Willd. [ 22 ] Anti‐inflammatory effects of UMB in animal models resemble those of non‐steroidal anti‐inflammatory drugs (NSAIDs), which render UMB an attractive alternative for evaluation in all pain models including neuropathic pain. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%